Capacity Building For Village Goverment And UMKM Through Community Service (Case Study: Community Service By Universitas Terbuka) - Dwi Putranto Riau (Syntax Corporation, 2022)
The village government, as a public organization that is close to the community and micro, small, and medium enterprises (UMKM), has a role in empowering UMKM but the limited capacity of the Village Government needs assistance from universities in increasing the organizational capacity of the Village Government and UMKM. UMKM data in 2019 amounted to 65.47 million. In detail, as many as 64.6 million units are micro-enterprises. A total of 798,679 units are small businesses. The proportion is 1.22% of the total UMKM in the country. Small enterprises are UMKM that need to be assisted and facilitated by universities in community service because few UMKM businesses are thriving and need to be empowered. With other similar products.This study aims to determine the contribution of the Open University in the aspect of the Tri Dharma College of community service by increasing the capacity of the Village Government and empowering UMKM through increasing business capital, product innovation, digital marketing, branding, bookkeeping, customer loyalty, and business licenses.The method used in this research is descriptive qualitative. Primary data is collected through discussion group forums and dialogues at the Village Government and UMKM workshop locations, and secondary data through websites, mass media, journals, books, and others. Data analysis involves data reduction steps, data presentation, and drawing conclusions or verification.The results of the study show that the capacity of the village government increases, and the empowerment of UMKM businesses by the Open University develops by the problems of UMKM and can compete with other similar products.